The Council of Europe and the International Relations (Czech Journal of International Relations, 2002)
Uwe Holtz (Hrsg.): 50 Jahre Europarat. 1. Aufl. Schriften des Zentrum für Europäische Integrationsforschung. Bd. 17. Baden-Baden: Nomos, 2000, 377 stran, ISBN 3-7890-6423-8 (signatura knihovny ÚMV 47 931).